Mathematical Literacy in Terms of Learning Independence of Junior High School Students - Ismail, Aldiansyah; Wardono, Wardono; Agoestanto, Arief (AlphaMath : Journal of Mathematics Education, 2024)
This study is a qualitative study with a descriptive approach that aims to describe the level of mathematical literacy of SMP Negeri 5 Semarang students from the perspective of learning independence. The study involved 6 students of class VII H from SMP Negeri 5 Semarang who were divided based on their level of learning independence, identified through questionnaire results as high, medium, and low learning independence. The data collection methods used were tests and interviews. The instruments used included mathematical literacy test, learning independence questionnaire, and interview guide. Data analysis was conducted through condensation, presentation, and conclusion drawing. The results showed that (1) Students with high learning independence managed to master all aspects of mathematical literacy satisfactorily, including communication, mathematization, representation, reasoning, problem-solving strategies, use of symbols, and mathematical tools; (2) Students with moderate learning independence were able to master most aspects of mathematical literacy well, with an emphasis on representation, reasoning, problem-solving strategies, use of symbols, and mathematical tools, although they still need improvement in communication and mathematization; (3) Students with low learning independence have not yet achieved competence in mathematical literacy